Analisa Performa Deteksi Marker pada AR Daspro Menggunakan Metode Fast Corner Detection - Neny Kurniati; Arda Surya Editya; Syahri Mu'min; Athika Dwi Wiji Utami (Jurnal Ilmu Komputer dan Desain Komunikasi Visual, 2018)
Augmented Reality (AR) is a technology that combines digital elements with the real world interactively. AR typically uses cameras to detect and track physical objects around it. Then, with the help of software, AR displays digital content, such as images, videos, or three-dimensional graphics on top of those physical objects. AR can be applied in everyday life, including the field of education, namely for learning Basic Programming. One of the engines to create an Augmented Reality application is Vuforia. In making augmented reality applications here not only using the Vuforia engine but also using the Unity application. The Basic Augmented Reality Programming (AR Daspro) application here is made to facilitate teaching in the Basic Programming course because most students find it very difficult to understand the concept of algorithms in the Basic Programming course. With the Augmented Reality application, it is expected to make it easier for students to understand algorithms. In this study, researchers will analyze how well the marker detection performance on the Vuforia Engine uses QR Code markers with the Fast Corner Detection method. If most Augmented Reality applications use image-based markers, but this time researchers want to try QR Codes as markers and later will be analyzed how the performance for marker detection.